Interrelation of psychophysiological indicators and physical readiness of qualified wrestlers - Yura Tropin; Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to establish the features and degree of interrelation of psychophysiological indicators and physical readiness among qualified wrestlers. Material & Methods: analysis of scientific and methodological information, generalization of best practical experience, psychophysiological methods of research, pedagogical testing, methods of mathematical statistics. Thirty qualified wrestlers took part in the research, at the age of 19-22. Results: the results of the study indicate the uniformity of the indices of simple and complex reactions, since the coefficient of variation lies in the range from 6,04% to 10,94%. The indicators of specific perceptions have a high coefficient of variation (from 15,56% to 48,82%), this is because specific perceptions more individually reflect the psychophysiological state of qualified wrestlers. Conclusions: it is determined that the most informative indicators of physical readiness are the tests of the wrestler's strength abilities, which have reliable connections with 11 psychophysiological indicators, followed by tests characterizing the strength endurance, with five statistically significant interrelations.